Cell-Penetrating Peptides as Delivery Enhancers for Vaccine - Jiang, Yuhong; Li, Man; Zhang, Zhirong; Gong, Tao; Sun, Xun (Current Pharmaceutical Biotechnology, 2014)
The poor permeability of cellular membrane is one of the principal hurdles of most drug administrations including vaccine system, consequently impairing drug efficiency. In order to address this natural barrier, cell-penetrating peptides (CPPs) have been developed to facilitate molecular cargos to enter cells. CPPs, generally short peptides with 5-30 amino acids, can be classified in to cationic, amphipathic and hydrophobic types according to physical-chemical properties. In this review, different processes of antigen uptake, subsequent processing and presentation of CPP-based vaccine are comprehensively summarized despite precise mechanisms are not still established. Some experimental factors such as cell types, concentration of CPPs and antigenic cargos have been reported to affect antigen uptake orientation. Moreover, this review discusses different antigenic cargos where CPPs can transport for vaccine delivery as well as the application of CPPs in vaccine system via different administration routes like transdermal, subcutaneous and mucosal immunization.
Keywords: antigenic cargo